Clustering Analysis of Internal and External Factors Affecting Post-Pandemic Study Duration in XYZ Educational Institution Using the Orange Application: Prediction of The Influence of Internal and External Factors on Study Duration - Muluk, Imelda; Widyasari, Yohana Dewi Lulu; Amelia, Riska (Jurnal Teknologi Informasi dan Pendidikan, 2023)
The COVID-19 pandemic has had a significant impact on various economic sectors in Indonesia, including the education system. Consequently, the educational landscape has undergone substantial changes, such as the shift from traditional classroom instruction to online learning. All students, regardless of their academic or non-academic backgrounds, have benefited from this transition in numerous ways. We are interested in identifying the most crucial factors that determine long-term learning outcomes and how academic and non-academic factors influence students' academic performance. The study will be conducted in October 2022 at SMK Negeri 6 Pekanbaru, and 529 out of 1400 participants will be randomly selected. We will use a Google Form with 22 questions to collect quantitative data.